Awareness and acceptance of postpartum intrauterine contraceptive devices amongst women in reproductive age group in an urbanized village of South Delhi - M., Suresh; Smanla, Shalini; Srivastava, Namita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: In India, grappling with a population surge, about 48.1 million pregnancies are unintended, highlighting the critical need for effective postpartum family planning (PPFP) to prevent adverse outcomes. Despite the postpartum intrauterine contraceptive devices (PPIUCD) benefits as a non-hormonal, reversible contraceptive, its uptake is hindered by various barriers. This study examines the awareness and acceptance of PPIUCD among women in the reproductive age group of South Delhi. Methods: This observational cross-sectional study was conducted at the field practice area under the Department of Community Medicine, Vardhman Mahavir Medical College and Safdarjung Hospital, New Delhi. Under this study, 190 women of reproductive age groups were included. The data was collected regarding awareness and acceptance of PPIUCD. The reason for acceptance and non-acceptance was collected. Data entered and analysed in Microsoft excel. Results: Out of 190 women of reproductive age,73% were aware of PPIUCD, and only 28% had accepted the PPIUCD. A statistically significant association between awareness and acceptance of PPIUCD was found. The most common reason for not accepting the PPIUCD was lack of awareness, followed by fear of complication. The reason for acceptance of PPIUCD was exposure to counselling and awareness that it was long-acting and reversible. The most common reason for the removal of PPIUCD is abdominal pain followed by bleeding. The statistically significant association between place of delivery and awareness and acceptance of PPIUCD was found. Conclusion: During the present study, it was found that Awareness and acceptance of PPIUCD was 73% and 28% of the women of reproductive age, respectively.